2014
DOI: 10.1590/0102-311x00156312
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in pregnancy and congenital syphilis in Amazonas State, Brazil: an evaluation using database linkage

Abstract: This study analyzes notification of syphilis in pregnancy and congenital syphilis in Amazo- nas State, Brazil, from 2007 to 2009 and verifies underreporting in databases in the National Information System on Diseases of Notification (SINAN) and the occurrence of perinatal deaths associated with congenital syphilis and not reported in the Mortality Information System (SIM). This was a cross-sectional study with probabilistic record linkage between the SINAN and SIM. There were 666 reports of syphilis in pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
(14 reference statements)
5
9
0
22
Order By: Relevance
“…In Brazil, the poor quality and underreporting of health data greatly compromise the analysis of deaths, especially with regard to fetal and early neonatal deaths [14,15]. The present study found a high proportion of underreporting of fetal and neonatal deaths due to CS in both information systems (SIM and Sinan).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In Brazil, the poor quality and underreporting of health data greatly compromise the analysis of deaths, especially with regard to fetal and early neonatal deaths [14,15]. The present study found a high proportion of underreporting of fetal and neonatal deaths due to CS in both information systems (SIM and Sinan).…”
Section: Discussionmentioning
confidence: 59%
“…A recent study in the state of Amazonas also found significant underreporting of CS as a cause of fetal or infant death. That study also found CS-related mortality that has probably been caused by this disease in the city [15]. …”
Section: Discussionmentioning
confidence: 84%
“…Os dados atuais sobre a SC no Brasil são provenientes do Sistema de Informação de Agravos de Notificação (SINAN), que apresenta subnotificação e elevado percentual de informações ignoradas ou em branco (4,(10)(11)(12). Isso limita o uso desse sistema em estudos sobre incidência e fatores relacionados ao aumento da SC.…”
unclassified
“…Isso limita o uso desse sistema em estudos sobre incidência e fatores relacionados ao aumento da SC. Entretanto, esse déficit pode ser compensado pelo relacionamento com outros sistemas de informação em saúde, como o Sistema de Informações sobre Nascidos Vivos (SINASC), o Sistema de Informações sobre Mortalidade (SIM) e o Sistema de Informações Hospitalares (SIH), aumentando a completude e a confiabilidade dos dados (10,13). Por sua vez, a análise de séries temporais (12,13,14) pode revelar não só a evolução da incidência, mas também fatores associados às mudanças nos padrões de distribuição do agravo (15), sendo de grande utilidade para agravos de difícil controle, como a SC.…”
unclassified
“…Apesar da melhora na disponibilidade e qualidade das informações do Sinan, grande número de casos não é notificado, com subnotificação que varia de 25% a 64% 11,15 . Quanto à subnotificação no Sistema de Informações sobre Mortalidade (SIM) especificamente para SC, um estudo mostrou que dos 20 óbitos encontrados no Sinan, apenas dois foram registrados no SIM 16 , o qual constitui uma fonte alternativa de dados, fornecendo causas básica, intermediária e imediata da morte, que devem estar ligadas em uma sequência de causa e efeito. Investigações de óbitos, especialmente os maternos e infantis, são preconizadas e incentivadas pelo Ministério da Saúde (MS) e um dos objetivos é estabelecer a melhor sequência de eventos mórbidos que levou à morte, para esclarecer qual a participação de fatores modificáveis que contribuíram para a sua ocorrência 5 .…”
Section: ▄ Introduçãounclassified